Hierarchical TiN‐Supported TsFDH Nanobiocatalyst for CO2 Reduction to Formate. Issue 15 (5th August 2021) - Arena, Federica; Giuffredi, Giorgio; Perego, Andrea; Donini, Stefano; Guzmán, Hilmar; Hernández, Simelys; Stancanelli, Eduardo; Cosentino, Cesare; Parisini, Emilio; Di Fonzo, Fabio
Abstract: The electrochemical reduction of CO2 to value‐added products like formate represents a promising technology for the valorization of carbon dioxide. We propose a proof‐of‐concept bioelectrochemical system (BES) for the reduction of CO2 to formate. For the first time, our device employs a nanostructured titanium nitride (TiN) support for the immobilization of a formate dehydrogenase (FDH) enzyme. The hierarchical TiN nanostructured support exhibits high surface area and wide pore size distribution, achieving high catalytic loading, and is characterized by higher conductivity than other oxide‐based supports employed for FDHs immobilization. We select the oxygen‐tolerant FDH from Thiobacillus sp. KNK65MA ( Ts FDH) as enzymatic catalyst, which selectively reduces CO2 to formate. We identify an optimal TiN morphology for the enzyme immobilisation through enzymatic assay, reaching a catalyst loading of 59 μg cm −2 of specifically‐adsorbed Ts FDH and achieving a complete saturation of the anchoring sites available on the surface. We evaluate the electrochemical CO2 reduction performance of the TiN/ Ts FDH system, achieving a remarkable HCOO − Faradaic efficiency up to 76 %, a maximum formate yield of 44.1 μmol mg −1 FDH h −1 and high stability. Our results show the technological feasibility of BES devices employing novel, nanostructured TiN‐based supports, representing an important step in the optimization of these devices. Abstract : Nanostructured Hybrid Electrocatalyst : A proof‐of‐concept bioelectrochemical system employing a hierarchical titanium nitride (TiN) support and an oxygen‐tolerant formate dehydrogenase catalyst from Thiobacillus sp. KNK65MA is reported for CO2 electroreduction to formate. By tuning the pore profile down to nanometer scales and by optimizing the surface area of the hierarchical TiN, an optimal binding with the enzyme is achieved, leading to a formate Faradaic efficiency up to 76 %, a gravimetric product yield of 44.1 μmol mg −1 FDH h −1 and high stability.